EVALUATION OF WATER ALLOCATION IN SEKAMPUNG SYSTEM /RR/GATION AREA USING ENTROPY WEIGHTÂ TOPSIS METHOD - Dwi Caesar Humaedi, Muhammad
Sekampung system irrigation area is one of the national rice barns in Lampung Province with a functional area of 55,373 hectares, and irrigation obtains a water supply from the Batutegi Dam which is 80 km away. So far, in the Sekampung System irrigation area, the system only applies 2 planting seasons throughout the year, this is very ironic considering that in the Sekampung system irrigation area, the system has been guaranteed by a regulator in the form of a reservoir. For this reason, an evaluation is carried out by considering 3 criteria, namely economic, social and environmental criteria related to the allocation that has been carried out for 10 years. Several methods can be applied to this research such as TOPSIS and Entropy Weight, where TOPSIS will try to resolve conflicts that will occur between the 3 criteria, TOPSIS will also be assisted by Entropy weight to obtained the weight on each criterion, this study will also use KP Irrigation as a guide to do research. The results of the study show that in the Sekampung Irrigation Area the system has the potential to apply 3 planting seasons, and one of the criteria is also determined as the best criterion according to TOPSIS.